Addressing Sexual Violence Related Trauma in Eastern DRC with Cognitive Processing Therapy - Bass, Judith; Bolton, Paul; Kaysen, Debra; Griffith, Shelly; Murray, Sarah; Cetinoglu, Talita; Robinette, Katie; Guimond, Marie-France; Wachter, Karin; Annan, Jeannie (World Bank, Washington, DC, 2017)
Sexual violence (SV) is recognized as a significant problem in the Democratic Republic of the Congo (DRC). SV can contribute to high levels of mental health symptoms, impaired functioning, and experiences of social stigmatization in female survivors, many of whom also face extreme economic hardship and poverty. This report provides results addressing the impact of a mental health intervention, cognitive processing therapy (CPT), on specific domains of social, physical, and economic functioning, and on the reduction of mental health problems, including depression, anxiety, and feelings of stigma and shame, associated with being an SV survivor.